Fully discrete explicit locally entropy-stable schemes for the compressible Euler and Navier–Stokes equations. (1st September 2020) - Ranocha, Hendrik; Dalcin, Lisandro; Parsani, Matteo
Abstract: Recently, relaxation methods have been developed to guarantee the preservation of a single global functional of the solution of an ordinary differential equation. Here, we generalize this approach to guarantee local entropy inequalities for finitely many convex functionals (entropies) and apply the resulting methods to the compressible Euler and Navier–Stokes equations. Based on the unstructured h p -adaptive SSDC framework of entropy conservative or dissipative semidiscretizations using summation-by-parts and simultaneous-approximation-term operators, we develop the first discretizations for compressible computational fluid dynamics that are primary conservative, locally entropy stable in the fully discrete sense under a usual CFL condition, explicit except for the parallelizable solution of a single scalar equation per element, and arbitrarily high-order accurate in space and time. We demonstrate the accuracy and the robustness of the fully-discrete explicit locally entropy-stable solver for a set of test cases of increasing complexity. Highlights: Generalization of the relaxation methods to guarantee local entropy inequalities. Application to an h p -adaptive compressible Navier–Stokes solver. Arbitrarily high-order accurate in space and time discretizations.